The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1159/000464119
|View full text |Cite
|
Sign up to set email alerts
|

Raf Kinase Inhibitor Protein Attenuates Ischemic-Induced Microglia Cell Apoptosis and Activation Through NF-κB Pathway

Abstract: Background: Acute ischemic stroke is one of the most important factors leading to disability and death with the characterization of accumulated neuron death and injured supportive neurovascular structures. Raf-1 kinase inhibitory protein (RKIP) is a key molecule in cell response to survival or death stimuli. However, the role of RKIP in stroke is worthy to be further studied. Methods: We used lentivirus mediated RKIP knockdown and overexpression to investigate the effect of RKIP on animal models of focal cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 41 publications
3
14
0
Order By: Relevance
“…Peroxynitrite permeates lipid layers, with peroxidation of membrane lipids, mediating nitration of tyrosine residue, inhibiting tyrosine phosphorylation, and thereby affecting cellular signal transduction. 51 Downregulation of PEBP and concomitant dementia was reported in rat brain samples exposed to hypoxia. 45 In the current study, combined use of LEV and WJ-MSCs was the most effective regimen as regard infarction volume and functional memory test.…”
Section: Discussionmentioning
confidence: 99%
“…Peroxynitrite permeates lipid layers, with peroxidation of membrane lipids, mediating nitration of tyrosine residue, inhibiting tyrosine phosphorylation, and thereby affecting cellular signal transduction. 51 Downregulation of PEBP and concomitant dementia was reported in rat brain samples exposed to hypoxia. 45 In the current study, combined use of LEV and WJ-MSCs was the most effective regimen as regard infarction volume and functional memory test.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that inflammatory response runs through the pathological development of cerebral ischemia-reperfusion and is one of the main causes of neuronal death [ 38 ]. Elevated proinflammatory cytokines aggregate a large number of inflammatory cells which secrete excessive inflammatory cytokines and aggravate brain damage [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear‐κB is the major nuclear transcription factor, and its activation usually stimulates inflammatory signalling pathways in microglia. Activated microglia, with a high expression of NF‐κB, promote the formation of an inflammatory microenvironment and damage to neurons or oligodendrocytes (Cherry, Olschowka, & O'Banion, ; Murugan, Sivakumar, Lu, Ling, & Kaur, ; Su, Zhang, Chen, Zhu, & Ma, ). Furthermore, it has been reported that inflammatory cells play an important role in neurodegenerative diseases via release of various pro‐inflammatory molecules (Calabrese et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear-B is the major nuclear transcription factor, and its activation usually stimulates inflammatory signalling pathways in microglia. Zhu, & Ma, 2017). Furthermore, it has been reported that inflammatory cells play an important role in neurodegenerative diseases via release of various pro-inflammatory molecules (Calabrese et al, 2018).…”
Section: Discussionmentioning
confidence: 99%